A Roadmap for CANS Validation. (29th December 2020) - Kraus, David R.
Abstract: In nearly every jurisdiction, juvenile or family courts will be using the Child and Adolescent Needs and Strengths (CANS) tool to assess whether children can safely be treated in family‐like settings to meet federal Family First Prevention Services Act (FFPSA) requirements. Yet, a number of peer‐reviewed publications have raised serious concerns regarding the lack of CANS validation research. Rather than reject CANS, this article provides a roadmap for validating the tool with data that jurisdictions have already collected. Courts should require these three simple analyses before relying on the assessment.